50 years National Mosque, 1965-2015 = 50 tahun Masjid Negara, 1965-2015 - Azim Ab. Aziz; Azim Ab. Aziz (ATSA Architects, 2015)
This monograph is produced in conjunction with the Exhibition to celebrate the 50th year of the National Mosque (1965-2015), held at the Islamic Arts Museum, Kuala Lumpur, Malayisa 5th September to 13th October 2015.